Loyalty Program in the Pharmacy. Case of Construction and Implementation - Agnieszka Woś (Contemporary Economics)
This paper presents the process of construction the loyalty programs between pharmaceutical market that is shaped warehouse, pharmacy and patient. The examples of this loyalty programs in this article has confirm the opinion about programs as efficiency in the pharmaceutical environment in Poland.